Analysis of the Determinants of Burnout Among GoJek Ride Partners: The Role of Daily Incentives, Order Challenges, and Customer Behavior - Irwin Sukrisno Soegeng; Sonny Francisco Siboro; Syamsudin Syamsudin (Jurnal Multidisiplin Sahombu, 2026)
The rapid growth of app-based transportation services has transformed the working patterns of ride-hailing drivers, while simultaneously increasing the risk of work-related fatigue and burnout. Burnout among GoJek Ride partners may adversely affect psychological well-being, service quality, and driving safety. This study aims to examine the effects of daily incentives, order difficulty, and customer responsiveness on burnout among GoJek Ride drivers in the Greater Jakarta area (Jabodetabek). This research adopts a quantitative explanatory approach using a survey method. Data were collected through structured questionnaires distributed to 133 GoJek Ride drivers selected via purposive sampling. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis to assess both partial and simultaneous effects among variables. The findings indicate that daily incentives have a positive and significant effect on driver burnout, suggesting that target-based incentive schemes may increase work pressure when not accompanied by proportional workloads. Order difficulty shows the strongest positive influence on burnout, particularly related to travel distance, traffic conditions, and task complexity. Meanwhile, customer responsiveness does not significantly affect burnout. Collectively, the independent variables explain 51.5% of burnout variance. These results highlight burnout as a multidimensional issue shaped largely by operational and platform-related factors.